1998
DOI: 10.1074/jbc.273.38.24730
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Binding of High Mobility Group 1 Protein to UV-damaged DNA

Abstract: Binding of chromosomal high mobility group 1 protein (HMG1) to UV-damaged DNA has been studied with oligonucleotides containing a single dipyrimidine site for formation of UV photolesions. Irradiation of an oligonucleotide with unique TT dinucleotide resulted in generation of cyclobutane pyrimidine dimer with no evidence for induction of (6-4) photoproducts, whereas the analysis of irradiated TC-containing oligonucleotide detected (6-4) photoproducts but not cyclobutane pyrimidine dimers. Mobility shift assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
64
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 55 publications
1
64
0
1
Order By: Relevance
“…The general function of acidic tail remains elusive despite its negatively regulations on HMG boxes. It downregulates the binding and bending ability of HMG boxes for linear DNA and distorted DNA although the binding affinity to DNA minicircles is unaffected (Bianchi et al, 1989;Pil et al, 1992;Stros et al, 1994;Pasheva et al, 1998;Lee et al, 2000). Several investigations have shown that the acidic tail binds to HMG boxes in vitro (Ramstein et al, 1999;Jung et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The general function of acidic tail remains elusive despite its negatively regulations on HMG boxes. It downregulates the binding and bending ability of HMG boxes for linear DNA and distorted DNA although the binding affinity to DNA minicircles is unaffected (Bianchi et al, 1989;Pil et al, 1992;Stros et al, 1994;Pasheva et al, 1998;Lee et al, 2000). Several investigations have shown that the acidic tail binds to HMG boxes in vitro (Ramstein et al, 1999;Jung et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…4A to 6) suggests a possible recruitment and therefore concentration of Gadd45 at sites where the nucleosomes have been weakened by either histone posttranslational modifications or DNA damage. While binding of sequence specific transcription factors is generally inhibited on UV-damaged templates (66,73), it is apparently increased for proteins recognizing altered DNA structure (8,25,39,45,63). For example, the high-mobility-group protein HMG1 has recently been shown to bind preferentially to UV-damaged DNA (45).…”
Section: Discussionmentioning
confidence: 99%
“…While binding of sequence specific transcription factors is generally inhibited on UV-damaged templates (66,73), it is apparently increased for proteins recognizing altered DNA structure (8,25,39,45,63). For example, the high-mobility-group protein HMG1 has recently been shown to bind preferentially to UV-damaged DNA (45). This chromosomal protein has also been shown to bind preferentially to other distorted DNA structures such as synthetic cruciform (4) and lesions formed by the anticancer drug cisplatin (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 overexpression has been reported in a variety of human cancers, including melanoma (9), pancreatic cancer, prostate cancer (10), colorectal cancer (11), and breast cancer (12). More importantly, HMGB proteins preferentially bind to cis-platinum(II)diaminedichloride (cisplatin)-modified DNA or to misincorporated nucleoside analogues and consequently inhibit nucleotide excision repair, which could be of great value in cancer treatment (13,14). Despite extensive characterization of the diverse roles of HMGB1 in cancer, much less is known of the signaling pathways of HMGB2, especially its relevance in carcinogenesis.…”
mentioning
confidence: 99%